2021
DOI: 10.1371/journal.pntd.0009420
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID–19 lockdown on dengue transmission in Sri Lanka; A natural experiment for understanding the influence of human mobility

Abstract: Background Dengue is one of the major public health problems in Sri Lanka. Its outbreak pattern depends on a multitude of drivers, including human mobility. Here we evaluate the impact of COVID–19 related mobility restriction (lockdown) on the risk of dengue in Sri Lanka. Methodology Two-stage hierarchical models were fitted using an interrupted time-series design based on the notified dengue cases, January 2015 to July 2020. In the first stage model, the district level impact was estimated using quasi-Poiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 20 publications
3
33
1
Order By: Relevance
“…People staying home due to lockdown may become easy prey for mosquitoes. Interestingly, movement restrictions (lockdowns) resulted higher incidence of dengue cases in Singapore, while the opposite impact was reported in Sri Lanka [ 18 , 19 ].…”
Section: Has the Dengue Outbreak Started In Dhaka City?mentioning
confidence: 99%
“…People staying home due to lockdown may become easy prey for mosquitoes. Interestingly, movement restrictions (lockdowns) resulted higher incidence of dengue cases in Singapore, while the opposite impact was reported in Sri Lanka [ 18 , 19 ].…”
Section: Has the Dengue Outbreak Started In Dhaka City?mentioning
confidence: 99%
“…Our study is also inline with a statistical analysis from Brazil finding a positive association of mobility restrictions with dengue cases 20 days later [ 49 ], and is similar to the finding that reductions in mobility due to the effects of fever can increase transmission [ 50 ]. Conversely, a study from Sri Lanka found a decreased risk of dengue during lockdown [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported similar ndings in Thailand, but not in Malaysia and Singapore [10]. On the contrary, an overall 88% reduction in risk of dengue (RR 0.12; 95% CI: 0.08-0.17) during the period of mobility restriction was observed in Sri Lanka [11]. Dengue serotype switch [10], increase in time spent inside residence [8], disruption of dengue surveillance and vector control activities due to restricted human movements [12] and compliance with social distancing policies have been suggested as potential factors that could explain the observed ndings.…”
Section: Introductionmentioning
confidence: 78%